Breast cancer risk in relation to history of preeclampsia and hyperemesis gravidarum: Prospective analysis in the Generations Study. Issue 4 (23rd March 2018) - Wright, Lauren B.; Schoemaker, Minouk J.; Jones, Michael E.; Ashworth, Alan; Swerdlow, Anthony J.
Abstract : Preeclampsia and hyperemesis gravidarum are pregnancy complications associated with altered sex hormone levels. Previous studies suggest preeclampsia may be associated with a decreased risk of subsequent breast cancer and hyperemesis with an increased risk, but the evidence remains unclear. We used data from the Generations Study, a large prospective study of women in the United Kingdom, to estimate relative risks of breast cancer in relation to a history of preeclampsia and hyperemesis using Cox regression adjusting for known breast cancer risk factors. During 7.5 years average follow‐up of 82, 053 parous women, 1, 969 were diagnosed with invasive or in situ breast cancer. Women who had experienced preeclampsia during pregnancy had a significantly decreased risk of premenopausal breast cancer (hazard ratio (HR) =0.67, 95% confidence interval (CI): 0.49–0.90) and of HER2‐enriched tumours (HR = 0.33, 95% CI: 0.12–0.91), but there was no association with overall (HR = 0.90, 95% CI: 0.80–1.02) or postmenopausal (HR = 0.97, 95% CI: 0.85–1.12) breast cancer risk. Risk reductions among premenopausal women were strongest within 20 years since the last pregnancy with preeclampsia. Hyperemesis was associated with a significantly increased risk of HER2‐enriched tumours (HR = 1.76, 95% CI: 1.07–2.87), but not with other intrinsic subtypes or breast cancer risk overall. These results provide evidence that preeclampsia is associated with a decreased risk of premenopausal and HER2‐enriched breast cancer and that hyperemesis, although not associated with breast cancer risk overall, may be associated with raised risk of HER2‐enriched tumours. Abstract : What's new? Although the link of preeclampsia and hyperemesis gravidarum with altered sex hormone levels is well established, relatively little is known about the association of these pregnancy complications with breast cancer risk. Here, the authors found that a history of preeclampsia decreased the risk of premenopausal breast cancer and tumors enriched for the receptor tyrosine‐protein kinase HER2. In contrast, hyperemesis gravidarum increased the risk to develop HER2‐enriched tumors, pointing to nuanced differences of sex hormone alterations during pregnancy with respect to breast cancer subtypes and menopausal status.